Ciągłość programowa a wizerunek partii politycznej. Przypadek Unii Polityki Realnej - Ćwiękała, Grzegorz (Polityka i Społeczeństwo, 2021)
The stability of the political programmes and election platforms and image of politicians is a very important research question in political science. The issues are also very important components of the voters’ decision making process. The voters judge the potential of politicians this way. The Real Politics Union is attached to liberal and conservative conceptions and cannot reach higher levels of awareness of voters and also cannot achieve regular election success. There are two kinds of obstacles, with the first being the image of the party and its leaders (tenacity, stubbornness, lack of confidence) and the second are the several objective elements (parties financing system, media silence, the electoral system). The article tries to give a partial answer to the problem of the functioning of small, extra-parliamentary parties and their efforts to enter the mainstream of Polish political arena.